ANALISIS PENGARUH SUKU BUNGA, DANA PIHAK KETIGA, DAN MODAL TERHADAP PERTUMBUHAN KREDIT PADA PT. BPR CIKARANG RAHARJA PERIODE 2010-2014 - Akromul Ibad, MM (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2015)
This study discusses about a Â whether the factors of interest rates, third party funds, and core capital effect on credit growth at PT . BPR Cikarang Raharja period 2010-2014 .The data used in this study is the growth computed amount of credit, mortgage interest rates are calculated from credit interest rate average annual PT. BPR Cikarang Raharja. Total third party funds is the amount of savings and time deposits PT. BPR Cikarang Raharja. Meanwhile, the capital derived from financial statements PT. BPR Cikarang Raharja period 2010-2014. The analysis technique used is multiple linear regression analysis. From the research results can be concluded that the variable interest rate, third-party funds, and core capital as an independent variable does not significantly affect the growth of credit in PT. BPR Cikarang Raharja period 2010-2014.